Advances in Biomarkers - Barut, Sümeyye (Nova Science Publishers, Inc., 2026)
Developments in the field of biomarkers are opening new horizons in the diagnosis and treatment of diseases. Biomarkers offer important application areas such as the detection of the disease at an early stage, monitoring the response to the treatment, and fthe development of personalized treatment options. Thanks to advances in “-omic” technologies such as genomics, proteomics, and metabolomics, biomarkers have become more specific, sensitive, and reliable. These developments have the potential to revolutionize the management of complex diseases, particularly cancer, cardiovascular diseases, and neurological disorders. Especially with the integration of artificial intelligence technologies, developments in the field of biomarkers have gained momentum. Artificial intelligence (AI) and machine learning algorithms are automating and accelerating the processes of identification, analysis, and selection of the most clinically effective biomakers. Thanks to AI, it has become possible to analyze large and complex biological data sets and to discover critical biomarkers earlier in the diagnosis and treatment of complex diseases such as cancer, cardiovascular diseases, and neurological disorders. In addition, AI-supported prediction models strengthen personalized treatment approaches by determining the effects of biomarkers on disease progression with greater precision. Innovations in this field are accelerating the integration of biomarkers into clinical applications and laying the groundwork for revolutionary advances in health care. However, more research and clinical validations are needed for the integration of biomarkers into clinical use. Scientific innovations in this field are expected to make significant contributions to future health services. © 2026 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Biomarkers; Development; Diagnosis; Recent advances